First stage reconstruction following surgical excision of a large arteriovenous malformation of the lower lip and tongue (Pain medicine, 2025)
Arteriovenous malformations (AVMs) are rare congenital lesions caused by deformity of the blood vessels. Around half of the AVMs are found in the craniofacial area, presenting with a progressive high-
Keywords: Arteriovenous malformation; tongue; lower lip; vascular malformation; vascular anomaly